A montagem e a utilização de lunetas de baixo custo como experiência motivadora ao ensino de astronomia - Iachel, Gustavo [UNESP]; Bacha, Marcelo Gomes [UNESP]; de Paula, Marina Pereira [UNESP]; Fernandes Scalvi, Rosa M. [UNESP] (Soc Brasileira Fisica, 2009)
This work reports on an experience of continual development courses for in-service teachers from some high schools of Bauru's (SP) region, for whom a specific workshop on assembling of refractor telescopes has been carried out in order to supplement their knowledge in astronomy. In the current article, the importance of the practice (or "knowing") in the context of their academic formation is discussed as well as some steps on the assembling of low cost refractor telescopes are described. The main results obtained from the participation of these teachers in the proposed activities are also presented.
The assembling and usage of low-cost refractor telescopes as motivating experience in astronomy education
Keywords: astronomy; refractor telescopes; optics teaching